Hypertension in Renal Transplant Recipients: Role of Bilateral Nephrectomy - Cohen, Simon L. (1973)
Of 81 transplanted kidneys which functioned for six months or more 59 were transplanted to bilaterally nephrectomized recipients and 22 to recipients who retained their own kidneys. There was an excess of hypertension in the non-nephrectomized group (17/22) as compared to 24/59 in the nephrectomized patients, though renal function was better in the non-nephrectomized group. Hypertension became much easier to control in two of the four non-nephrectomized recipients in whom bilateral nephrectomy was performed after transplantation when renal function was good.